THE HYPO-OSMOTIC SWELLING TEST IN FRESH GARUT RAM SPERMATOZOA - Nalley, W.M.M.; Arifiantini, R.I. (Diponegoro University, 2013)
The study was aimed to determine the optimal time to evaluate the maximum numbers of swollensperm after expose to hypo-osmotic solution for testing membrane integrity in fresh garut ram semen. Atotal of 24 ejaculate samples from eight sexually mature garut ram were collected using artificial vagina.After macroscopic evaluation, 10 μL undiluted semen was gently mixed in each of the 2 mL hypoosmoticsolution and incubated at 37oC for 1 hour. Two hundred of coil and non-coiled sperm wereobserved from five different fields every 15 minutes. Results demonstrated that the maximumpercentage of coiling sperm positive to HOS test was at 30 minutes and no differences among 8 garutrams used.